Effect of Tier Surface Structure on Non‐wetting Materials and Robust Superamphiphobic Surface. Issue 44 (10th December 2019) - Fan, Beibei; Wang, Tao; Jia, Xueying; Ji, Lvlv; Lv, Chang; Wang, Sheng
Abstract: Surface structure is a key factor for the non‐wettability, that's because different surface tier structure can catch different numbers of air‐pockets. The weak hierarchical surface structure limits the application of non‐wetting materials. In this work, the different tier structure Te@C, Te@C‐SiO2, SNTs are prepared to characterize the influence of tier structure on the non‐wettability and N2 adsorption–desorption isotherms are used to characterize the air‐pockets. The aluminum dihydrogen phosphate is used to strength the robustness of SiO2 NTs superamphiphobic surface. The results indicate that the more tiers of surface structure have a higher SBET, higher SBET ensure enough air‐pockets, which can make more contributions to the non‐wettability. The prepared robust superamphiphobic surface shown extreme robustness, and after 50 cycles of sandpaper abrasion, it is still super‐repellent to hexadecane. Abstract : The different tier structure Te@C, Te@C‐SiO2, SNTs are prepared to characterize the influence of tier structure on the non‐wettability and N2 adsorption–desorption isotherms are used to characterize the air‐pockets. The aluminum dihydrogen phosphate is used to strength the robustness of SiO2 NTs superamphiphobic surface. The results indicate that the more tiers of surface structure have a higher SBET, higher SBET ensure enough air‐pockets, which can make more contributions to the non‐wettability.